Epitaxially grown semi-vertical and aligned GaTe two dimensional sheets on ZnO substrate for energy harvesting applications. (February 2019) - Chen, Zuxin; Chu, Sheng; Chen, Jiapeng; Chen, Hao; Zhang, Jingtao; Ma, Xinzhou; Li, Qiuguo; Chen, Xuechen
Abstract: Two-dimensional (2D) materials are particularly interesting for increasing the efficiency of optoelectronic devices. Here, we report a solar cell structure based on 2D GaTe nanosheets on m -plane ZnO substrate. Specifically, the 2D GaTe nanosheets form a semi-vertical/tilted array to combine sufficient solar light absorption and efficient carrier conduction. The formed GaTe layer of about 70 nm and the basal plane have a tilted angle of 53 degrees with respect to the substrate. Such an alignment is found to be induced by the interface lattice mismatch between GaTe and ZnO. The heterojunction photovoltaic device achieves a power conversion efficiency (PCE) of 6.64% demonstrating that the controlled integration of 2D materials in 3D configurations is promising for increasing the efficiency in various kinds of energy devices. Graphical abstract: Highlights: Closely packed, tilted and epitaxial 2D GaTe nanosheets array are obtained on m -plane ZnO substrate. The grow mechanism of the epitaxial GaTe nanosheets is found to be domain-matching between GaTe and the ZnO substrate. The obtained structure ( p -GaTe/ n -ZnO) showed good photovoltaic response (reaching a PCE of 6.6%.).